Co-activation of rhythms during alpha band oscillations as an interictal biomarker of exploding head syndrome. (August 2020) - Fotis Sakellariou, Dimitris; Nesbitt, Alexander David; Higgins, Sean; Beniczky, Sandor; Rosenzweig, Jan; Drakatos, Panagis; Gildeh, Nadia; Murphy, Patrick Brian; Kent, Brian; Williams, Adrian John; Kryger, Meir; Goadsby, Peter J; et al.
Background: Exploding head syndrome is a rarely reported benign sensory parasomnia that may nonetheless have significant impact on patients' quality of life and their perceived well-being. To date, the mechanisms underlying attacks, characterised by a painless perception of abrupt, loud noises at transitional sleep-wake or wake-sleep states, are by and large unclear. Methods and results: In order to address the current gap in the knowledge of potential underlying pathophysiology, a retrospective case-control study of polysomnographic recordings of patients presenting to a tertiary sleep disorders clinic with exploding head syndrome was conducted. Interictal (non-attack associated) electroencephalographic biomarkers were investigated by performing macrostructural and event-related dynamic spectral analyses of the whole-night EEG. In patients with exploding head syndrome, additional oscillatory activity was recorded during wakefulness and at sleep/wake periods. This activity differed in its frequency, topography and source from the alpha rhythm that it accompanied. Conclusion: Based on these preliminary findings, we hypothesise that at times of sleep-wake transition in patients with exploding head syndrome, aberrant attentional processing may lead to amplification and modulation of external sensory stimuli.